Energy Management System for Hospital Building Using Genetic Algorithm - Mat Isa, Normazlina; Tan, Chee Wei; Yatim, A.H.M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Microgrid (MG) as well as energy management system (EMS) is undergoing an immense growth. A cogeneration, as one of MG topologies, needs an efficient controller to manage the supply-demand activity so that both sides can achieve their goals. The EMS plays a role as a supervisory controller to optimally dispatch the energy in order to satisfy the load demand. In this paper, EMS based on optimization approaches to minimize the operating cost of cogeneration system is presented. This study developed a cogeneration system that consists of grid-connected photovoltaic, fuel cell and battery. This system was adopted at hospital building, which was selected as a sample of load profile. An optimization problem was formulated by considering decision variables, input system parameters, objective function and constraints. Furthermore, the problems were solved using Genetic Algorithm. The viability of the optimization approaches was simulated in MATLAB environment.